2018
DOI: 10.1177/1350650118766794
|View full text |Cite
|
Sign up to set email alerts
|

Improved calculation of load-dependent gear losses by consideration of so far disregarded influences

Abstract: The topic of this study was subject to the efficiency calculation of gearboxes. Additional analyses were performed with regard to an existing calculation approach, to improve the calculation of load-dependent gear losses by so far disregarded influences. On the one hand, the influence of the driving direction was investigated. During this, the driving and driven test gears considered showed high differences of the specific sliding at tooth root and tooth tip. On the other hand, the influence of the change of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…Experimental investigationsFigure2shows the experimental results on the pitting lifetime for the lubricants LM 1 EP, LM 1 EPII, LM 1 EPIII, LM 1 PD and LM 1 ZP and light microscopic images of representative tooth flanks on the pinion.For pitting tests with LM 1 EP and LM 1 PD at the lower pinion torque of T 1 = 480 Nm, the tooth flank condition of the test gears are comparable and inconspicuous. In accordance toKadach et al (2015), no pitting was observed.…”
supporting
confidence: 69%
See 3 more Smart Citations
“…Experimental investigationsFigure2shows the experimental results on the pitting lifetime for the lubricants LM 1 EP, LM 1 EPII, LM 1 EPIII, LM 1 PD and LM 1 ZP and light microscopic images of representative tooth flanks on the pinion.For pitting tests with LM 1 EP and LM 1 PD at the lower pinion torque of T 1 = 480 Nm, the tooth flank condition of the test gears are comparable and inconspicuous. In accordance toKadach et al (2015), no pitting was observed.…”
supporting
confidence: 69%
“…For the investigations on the pitting lifetime at the standard FZG back-to-back gear test rig, test gears of type 17/18 with a short tip relief were used (Kadach et al, 2015;Güntner et al, 2017). A running-in with a pinion torque of T 1 = 370 Nm, a pinion rotational speed of n 1 = 210 rpm and an oil temperature of # oil = 60°C was performed for 10,000 load cycles of the pinion before each pitting test.…”
Section: Test Gears and Operating Conditionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hence, the load-dependent gear loss P LGP can be determined by subtracting the sum of the no-load losses and the load-dependent bearing loss P LBP from the measured total loss P L . As the test gearboxes have the same balanced gear pairs with the pitch point in the middle of the path of contact, the measured loss can be approximately halved to derive the load-dependent gear loss of one gearbox (Jurkschat et al , 2019).…”
Section: Methodsmentioning
confidence: 99%